Creating Sustainable Business: How Does It Happen? An Exploration of Motivators & Facilitators in Three Organizational Settings in the U.S. - Byerly, Robin T. (Archīum Ateneo, 2023)
Despite the fact that serious concerns regarding the deterioration of the environment and natural resources have been voiced for decades, current business and organizational approaches toward sustainability remain inadequate and substantially unsustainable. An important research question, therefore, has to do with understanding how to make positive behavior more prevalent in the face of many urgent global challenges. Newer business and organizational models that are significantly moving toward sustainability, for instance, serve as remarkable examples of such. What can we learn from them? This study seeks more specific answers to this broad question. How are modern organizations motivated to embrace sustainability initiatives in a genuine manner? How have they created their sustainable business models? How do they continue to sustain the initial momentum? What are the key factors that assist in the implementation of sustainability strategies? Lastly, how are they defining and achieving sustainability success? Answers to these questions were sought through an inductive and qualitative case research design that explored three quite different organizational settings, each pursuing sustainability objectives with advancing success and yet finding its own way in very different environments based on industrial, regulatory, and cultural influences. Nevertheless, several general characteristics seemed to accrue across organizational and industrial divides. A model for sustainability management, derived from the lessons learned in this study, is thus proposed.